THE ROLE OF LEGAL INSTITUTIONS IN PROTECTING COMMUNITY RIGHTS AMID PALM OIL PLANTATION GROWTH - Tiara Ramadhani; Khalid Vikriadi; Riky Ovaliansyah Harahap (Adisam Publisher, 2025)
This study analyzes the role of legal institutions in protecting the rights of local communities amid the massive growth of oil palm plantations in Indonesia. Using a qualitative socio-legal approach, the research was conducted through in-depth interviews, field observations, and documentation studies in areas with high intensity of agrarian conflicts. The results show that although national legal frameworks have regulated the recognition of land rights, public consultation, and dispute resolution mechanisms, their implementation is still far from effective. The weakness of the capacity of institutions such as BPN, local governments, and law enforcement officials causes the licensing process to be not transparent, land verification is slow, and dispute resolution does not provide substantive protection for the community. Non-state mechanisms such as the RSPO and ISPO have also not been able to be effective alternatives due to limited access, community advocacy capacity, and a more administrative focus on social justice. This study concludes that the main problem lies not in the absence of regulations, but in the weak institutional function in running, supervising, and enforcing the law. These findings contribute to the natural resource governance literature by emphasizing the importance of institutional reform, capacity building for dispute resolution, and expanding access to legal aid for affected communities as a step towards fairer and more sustainable palm oil governance